BALANCING FUNCTIONALITY AND SECURITY: A FRAMEWORK FOR IOT SOFTWARE INTEGRATION WITH THIRD-PARTY SERVICES IN CRITICAL SECTORS - Pavan Vovveti (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
263The rapid growth of the Internet of Things (IoT) ecosystem has led to an increased need for seamless integration between IoT software applications and third-party solutions across various industries. While offering significant benefits in terms of enhanced functionality and efficiency, this integration presents substantial challenges in maintaining robust security measures. This article explores the complexities of integrating IoT platforms with third-party services in smart cities, healthcare, and automotive sectors, focusing on ensuring secure authentication, authorization, and communications. We analyze the critical aspects of data privacy and security throughout the entire data lifecycle, from collection to deletion, in the context of IoT-third party integrations. The article addresses key challenges, such as scalability issues and potential security vulnerabilities introduced by these integrations. By examining case studies and current best practices, we propose a comprehensive framework for secure IoT integration that balances functionality with stringent security requirements. Our findings highlight the importance of robust API (Application Programming Interface) security, encryption protocols, and access control mechanisms in creating resilient IoT ecosystems. This article contributes to the growing body of knowledge on IoT security. It provides practical guidelines for organizations seeking to leverage third-party integrations while maintaining the integrity and confidentiality of their IoT platforms.